Waqf for socio-economic development: a perspective of Ibn Khaldun - LIstiana, Lisa; Syed Jaafar Alhabshi, Syed Musa; Harjunadhi, Agastya Widhi (Ibn Haldun University, 2020)
While waqf past significant contribution towards the welfare of society has been acknowledged, it is believed that waqf has potential to be the icon and esteemed institution to establish Islamic civilization and promote socio economic justice in this contemporary era. While more studies on waqf have been conducted, it is apparent that Western perspective dominates the discussion. Less literatures from well-known Muslim scholar is explored to gain the insight for waqf development. As such, with the spirit for waqf revival, this current study is going to fill this gap by exploring and relating to the perspective of Ibn Khaldun. Firstly, this paper is going to elaborate the perspective of Ibn Khaldun on the role of the State for socio-economic development. Secondly, it will elaborate the Ibn Khaldun’s perspective on how to promote moral values that warrant sustainable and fair environment in the society. Based on his perspectives, a recommended practice is proposed to promote waqf for socio-economic development. This study represents the pioneer work that attempts to elaborate waqf and Ibn Khaldun’s perspective to promote sustainable socio-economic development.